The Absence of Urease Enzymatic Activity of Helicobacter pylori Coccoid Form - Dwi Sulistya Dyah Jekti; Soewignjo Soemohardjo; Zainul Muttaqin (The Indonesian Society for Digestive Endoscopy, 2008)
Background: Helicobacter pylori (H. pylori) is a gram negative and pleomorphic bacteria that able to change its morphology according to the environment. The objective of the study was to determine the biochemical and some genetic characteristic of coccoid form of H. pylori induced by starvation, aerobiosis and antibiotic. Method: The material of the study is an isolate of spiral form of CagA positive H. pylori grown from gastric biopsy specimen of a patient with chronic gastritis. The CagA positive isolate was subcultured in liquid media containing the sheep sera. The sample was divided into three groups each group consist of 27 tube. Each tube contained 109 CFU of H. pylori bacteria/ml in 4 ml liquid media. So the experiment was performed in 3 replicates. In the first group of sample, coccoid form was induced by a prolonged culture under microaerophilic condition without the addition of fresh media, in the second group by aerobiosis, while in the third group by addition of 0.1 µg amoxycillin/ml cultured in microaerophilic condition. Periodic sampling was done every day to calculate the percentage of coccoid form, to observe the possibility to regrow the spiral form and for serial electron microscopic observation. One tube is picked up in every periodic sampling. In tubes containing antibiotic the periodic sampling was done one hourly. Detection of cagA and ureA gene was done by Polymerase Chain Reaction (PCR) with appropriate primers. Results: The time needed for the development of coccoid form: Length of time from the start of the experiment needed to reach 100% coccoid form was: 49 days in microaerophilic with starvation, 28 days in aerobiosis with starvation, and 13.5 days in antibiotic. result of biochemical test: Urease enzymatic activity was only positive in spiral form. All samples of coccoid form due to all the 3 stressors did not show any urease enzymatic the activity. PCR of ureA gene: All samples of spiral and coccoid form showed positive band of ureA gene and cagA gene. Western blot of protein CagA, urease A and urease B: Western blot analysis showed that in spiral form and all coccoid form band of urease A and urease B is clearly seen,while cagA in Western blot only clearly seen in spiral form but it is absent in cocoid form. Conclusion: Troughout the cycle of coccoid form the urease gene responsible for the production of urease and cagA gene responsible for virulence was in intact condition. However, despite the presence of urease protein in coccoid form the urease enzymatic activity was absent. This fact has several diagnostic and clinical implications. Keywords: urease enzymatic activity, coccoid form, Helicobacter pylori